Enhancing O2-permeability and CO2-tolerance of La2NiO4+δ membrane via internal ionic-path - Wei, Q.; Zhang, S.; Meng, B.; Han, N.; Zhu, Z.; Liu, Shaomin (Elsevier BV, 2018)
© 2018 Elsevier B.V. Novel La2NiO4+d-Sm0.2Ce0.8O1.9dual-phase hollow fiber membrane was developed via a combined phase inversion-sintering process. The enhanced O2-permeability is due to the existence of LNO and SDC interface crossing the composite membrane not only from the surface, but also from the bulkiness, which greatly promotes the oxygen ionic transport rates. Such dual-phase membrane shows great CO2-resistance without sacrificing the oxygen permeation flux value when swept by pure CO2compared with helium.